Ivan Kroneberg and theory of romantisism in Ukraine - Бовсунівська, Тетяна Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The essence of the proposed report is to overcome the white spots in the theory and history of Ukrainian romanticism, which is still sometimes regarded as an almost unfortunate Western reception, that is, in accordance with the Soviet pattern of interpretations, where Ukrainian romanticism was deprived of independent theoretical thinking. Undoubtedly, the fact of the influence of German philosophical idealism (Schelling, Schlegeli, Novalis, Schleiermaher, etc.) on the development of Ukrainian romanticism should not be denied, as the representatives of the French, Spanish, Italian, and others also suffered the same effect. romanticism, although nobody denies the peculiarity of their artistic and theoretical development. In this aspect, the personality of Ivan Kronoberg, who was not only known as a follower of the German School of Philosophical Knowledge, became one of the first theorists of Ukrainian romanticism. Thus, the work of Ivan Kronoberg at Kharkiv University was marked by a number of works (for example, "The content and form of graceful literature", "On the progress of art from ancient peoples", "Thoughts about the fine arts", etc.) and lectures that laid the foundations of Ukrainian romantic thinking and without which it would be impossible to make the Kharkov school of romantisism (by definition Agapiy Shamray). Among the ideas promoted by him, the most significant were: 1) the critique of the classical taste theory and his own system of pre-romantic aesthetics; 2) introducing the category of "originality" into the system of aesthetics and advocating its value; 3) the accent on the predominance of a genius over any aesthetic systems and the renunciation of the aristocracy of art; 4) Schelling's controversy on taste and imitation, the emphasis on the fact that the eternal spirit as the goal of any art can not fully manifest itself in temporary phenomena of art; 5) the critique of Herder and Jean-Paul in the classification of the concepts of aesthetics as a science and the presentation of their own approaches to systematization; 6) presentation of the philosophy of revelation as the most suitable for the cultural sphere; 7) problematization of the relation of aesthetics and ethics in favor of their unity; 8) spirit as an activity and a component of art - a completely romantic idea; 9) transcendence of the form and eternity of the content: the form is transcendental because it depends on the living creative spirit in the living stream of knowledge, and therefore, it will change as much and as much as it needs spirit; 10) justification of the category "divine" in aesthetics and in art; 11) aesthetics is regarded as a science of the artistic embodiment of Christian theogony; and the rest are not devoid of purely romantic expediency. The aesthetic views of I. Kronoberg significantly differ from the classical ones that were pronounced by his predecessors at the beginning of the nineteenth century (Philomaphitsky, Gonorsky, Maslov, Sklabovsky and others). By refracting the classic canons of taste, form, genre, he did not linger within the limits of polemical aesthetics, and proclaimed the laws of new art, not burdened with ancient canons, which presents the existence of the spirit and the truthfulness of which is consistent with the divine truth, which in art equates to the artistic ideal.